In-depth characterization of congenital Zika syndrome in immunocompetent mice : antibody-dependent enhancement and an antiviral peptide therapy - Camargos, Vidyleison N. (2019)
Background: Zika virus (ZIKV) infection during pregnancy may cause major congenital defects, including microcephaly, ocular, articular and muscle abnormalities, which are collectively defined as Congenital Zika Syndrome. Here, we performed an in-depth characterization of the effects of congenital ZIKV infection (CZI) in immunocompetent mice. Methods: Pregnant dams were inoculated with ZIKV on embryonic day 5.5 in the presence or absence of a sub-neutralizing dose of a pan-flavivirus monoclonal antibody (4G2) to evaluate the potential role of antibody-dependent enhancement phenomenon (ADE) during short and long outcomes of CZI. Findings: ZIKV infection induced maternal immune activation (MIA), which was associated with occurrence of foetal abnormalities and death. Therapeutic administration of AH-D antiviral peptide during the early stages of pregnancy prevented ZIKV replication and death of offspring. In the post-natal period, CZI was associated with a decrease in whole brain volume, ophthalmologic abnormalities, changes in testicular morphology, and disruption in bone microarchitecture. Some alterations were enhanced in the presence of 4G2 antibody. Interpretation: Our results reveal that early maternal ZIKV infection causes several birth defects in immunocompetent mice, which can be potentiated by ADE phenomenon and are associated with MIA. Additionally, antiviral treatment with AH-D peptide may be beneficial during early maternal ZIKV infection.